Effect of endocrine disruptors on mammalian fertility - Pěknicová, Jana; Buckiová, Daniela; Boubelík, Michael; Nováková, Vendula (Abstracts of the 2nd Czech and International Congress of Andrology, 2007)
Many chemicals released into the environment can interfere with the action of the endocrine system through diverse mechanisms in animals and humans. This includes chemicals that occur naturally in plants such as phytoestrogens and also manmade chemicals (xenoestrogens). In our study we selected xenoestrogens (bisphenol-A (BPA), p-nonylphenol (NP), diethylstilbestrol (DES)) and phytoestrogens (genistein (GEN), resveratrol (RES)). All these pollutants represent of endocrine disruptors (ED). The effect of BPA, NP, DES, GEN and RES on the body weight, weight of different organs, sperm acrosomal status and in vivo fertility of CD1 mice was tested in a multigenerational study. The adult parental generation of mice and F1 and F2 generations were exposed to selected drugs for all their life. BPA and NP had a negative effect on offspring born of mice, on reproductive organs, and acrosome integrity of mice spermatozoa. Different effect was found in P, F1 and F2 generations. The fertility of mice exposed to DES was disrupted, especially in the first generation. Contrary to that, treatment by GEN and RES had no effect on fertility of CD1 mice but had some effect on reproductive parameters except of sperm integrity. Monoclonal antibodies against intra-acrosomal sperm proteins were used as biomarkers of sperm damage.